Race and races / Richard A. Goldsby - Goldsby, Richard A. (1971)
A synopsis, race, races, the depth of diversity, evolution and man, the origin of reces, rece and mental ability; this timely new book examines the reality and meaning of race within a framework of modern biological knowledge and concepts, written for the beginning student, it provides relevant, nontechnical introduction clearly explained when they are required by the discussion, the book's full exploration of human diversity demonstrates that the differences are trivial.